Loading [MathJax]/jax/element/mml/optable/GeneralPunctuation.js

Monday, November 24, 2014

2014/105) show that all terms of \dfrac{107811}{3}, \dfrac{110778111}{3} and \dfrac{111077781111}{3} ... are pefect cubes

let us look at 1st few terms

1st term = \dfrac{107811}{3} = \dfrac{1 * 10^5 + 77 * 10^2 + 111}{3} 
2nd term = \dfrac{110778111}{3} = \dfrac{11 * 10^7 + 777 * 10* 3 + 1111}{3}
3rd term = \dfrac{111077781111}{3} = \dfrac{111 * 10^9 + 7777 * 10^4 + 11111}{3}

so nth term = \dfrac{(10^n- 1) * 10^{2n+3} + 7 * 10^{n+2} -1)* 10^{n+1} + (10^{n+2} - 1)}{3*9}
=\dfrac{ (10^n-1) * 1000 * 10^{2n} + 7 *( 100 * 10^n - 1)(10 * 10^n) + (100 * 10^n - 1)}{27}
=\dfrac{1000 * 10^{3n} - 1000 * 10^{2n} + 7 *1000 * 10^{2n} - 7 *10 * 10 ^n + 100 * 10^n - 1}{27}
= \dfrac{1000 * 10^3n - 300 * 10 ^2n + 30 * 10 ^n -1}{27}
= \dfrac{10^{3n+3} - 3 * 10^{2n+2} + 3 * 10^{n+1} -1}{27} = \dfrac{(10^{n+1} - 1)^3}{27}

so nth term = (\dfrac{10^{n+1} -1}{3})^3

which is a perfect cube


 

Wednesday, November 19, 2014

Q2014/104) find the degree of polynomial (x+\sqrt{x^3-1})^7 + (x-\sqrt{x^3-1})^7

We have
(a+b)^7=a^7+7a^6b+21a^5b^2+35a^4b^3+35a^3b^4+21a^2b^5+7ab^6+b^7
also  
(a-b)^7=a^7-7a^6b+21a^5b^2-35a^4b^3+35a^3b^4-21a^2b^5+7ab^6-b^7

so (a+b)^7 + (a-b)^7= 2a^7+42a^5b^2+70a^3b^4+14ab^6

So (x+\sqrt{x^3-1})^7 + (x-\sqrt{x^3-1})^7
= 2 x^7+42x^5(x^3-1)+70x^3(x^3-1)^2+14x(x^3-1)^3

now the term with highest power of x is x^{10} and so 10 is degree of polynomial 

Saturday, November 8, 2014

2014/103) prove that \cot 2x - \tan 2x = 2\cot 4x

LHS = \dfrac{\cos 2x }{\ sin 2x}- \dfrac{\sin 2x}{\cos 2x}
= \dfrac{\cos^2 2x - \sin^2 2x}{\sin 2x\cos 2x}
= \dfrac{\cos 4x}{\sin 2x\cos 2x}
= \dfrac{2\cos 4x}{2\sin 2x\cos 2x}
= \dfrac{2 \cos 4x}{\sin 4x}
= 2 \cot 4x

2014/102) show that \lfloor(\sqrt{n} +\sqrt{n+1}\rfloor= \lfloor(\sqrt{4n+2}\rfloor


we realise that n(n+1) = (n+\dfrac{1}{2})^2 - \dfrac{1}{4}
so \sqrt{n(n+1)}\lt(n+\dfrac{1}{2})
clearly n\lt\sqrt{n(n+1)}

so

we have
(\sqrt{n} + \sqrt{n+1})^2 = n + n+ 1 + 2 \sqrt{n(n+1)}
= 2n +1 + 2 \sqrt{n(n+1)}
>2n+ 1 + 2 n or > 4n+ 1

and = 2n +1 + 2 \sqrt{n(n+1)}2n +1 + 2 (n + \dfrac{1}{2})
or <  (4n + 2)
so (4n+1)\lt(\sqrt{n} + \sqrt{n+1})^2\lt(4n+2)

because  4n+2 is not a perfect square

we have \lfloor(\sqrt{4n+1}\rfloor = \lfloor(\sqrt{4n+2}\rfloor
and as (\sqrt{n} + \sqrt{n+1})^2 is between 4n + 1 and 4n +2 we have

\lfloor(\sqrt{4n+1}\rfloor = \lfloor(\sqrt{4n+2}\rfloor= \lfloor(\sqrt{n} +\sqrt{n+1}\rfloor

Thursday, November 6, 2014

2014/101) If \sin\theta = k \sin(\theta + 2\alpha) prove that \tan (\theta + \alpha) = \dfrac{1+k}{1-k}\tan \alpha

we have
k = \dfrac{sin\theta}{\sin(\theta + 2\alpha)}
using componendo dividendo
 \dfrac{k+1}{k-1} = \dfrac{\sin\theta+\sin(\theta + 2\alpha)}{\sin\theta-\sin(\theta + 2\alpha)}
=\dfrac{ 2 \sin(\theta + \alpha ) \cos \theta}  {-2 \cos (\theta + \alpha) \sin \theta}
= \dfrac{ - \tan(\theta + \alpha )}{\tan \theta}

hence \dfrac{1 + k} {1- k} = \dfrac{\tan(\theta + \alpha )}{\tan \theta}

or  \dfrac{1 + k} {1- k}\tan \theta = \tan(\theta + \alpha) 
proved

Wednesday, November 5, 2014

Q2014/100) show that \sqrt[3]{45 + 29\sqrt2} + \sqrt[3]{45 - 29\sqrt2} is rational

it is as below
 x=\sqrt[3]{45 + 29\sqrt2} +  \sqrt[3]{45 - 29\sqrt2}
or
x-\sqrt[3]{45 + 29\sqrt2} -  \sqrt[3]{45 - 29\sqrt2}= 0

using a+b+c = 0 => a^3+b^3+ c^3 = 3abc
we get
x^3-(45 + 29\sqrt2) - (45 - 29\sqrt2)= 3 x\sqrt[3]{(45 + 29\sqrt2)(45 - 29\sqrt2)}
or
x^3-90= 3x\sqrt[3]{45^2 - 2 * 29^2}
or x^3-90 = 21x
or x^3 - 21x - 90 = 0
or (x-6)(x^2+6x+ 15) = 0
has one real root = 6 and 2 complex roots

hence given expression = 6 which is real

Tuesday, November 4, 2014

2014/99 ) find the 50th smallest number which is coprime to 987

First we need to factor 987
987 = 3 * 329 = 3 * 7 * 47

to find a number which is coprime to 987 it should be co-prime to 3,7, and 47

now 1 is not coprime to any number so we need to find the 51st number which is  not divisible by 3 7 or 47

for x the numbers below or same as not divisible by 3 7 and 47 are

f(x) =x-\lfloor\dfrac{x}{3}\rfloor-\lfloor\dfrac{x}{7}\rfloor-\lfloor\dfrac{x}{47}\rfloor+\lfloor\dfrac{x}{3*7}\rfloor+\lfloor\dfrac{x}{3* 47}\rfloor+\lfloor\dfrac{x}{7*47}\rfloor- \lfloor\dfrac{x}{3 * 7 * 47}\rfloor

or f(x) =x-\lfloor\dfrac{x}{3}\rfloor-\lfloor\dfrac{x}{7}\rfloor-\lfloor\dfrac{x}{47}\rfloor+\lfloor\dfrac{x}{21}\rfloor+\lfloor\dfrac{x}{141}\rfloor+\lfloor\dfrac{x}{329}\rfloor- \lfloor\dfrac{x}{987}\rfloor

or f(x) =x-\lfloor\dfrac{x}{3}\rfloor-\lfloor\dfrac{x}{7}\rfloor+\lfloor\dfrac{x}{21}\rfloor-\lfloor\dfrac{x}{47}\rfloor+\lfloor\dfrac{x}{141}\rfloor+\lfloor\dfrac{x}{329}\rfloor- \lfloor\dfrac{x}{987}\rfloor


for estimating we take x-\dfrac{x}{3}=\dfrac{2x}{3}=51 or x = 76 ( rounded)

so f (x) = 76  - 25 - 10 + 3 = 44
we are falling short by 7

so we add 11 as it is 7 * 3/2 rounded

so we get x = 87 but as 87 is not coprime we take 88

f(88) = 88 - 29 - 12 + 4 - 1 = 50

so we take next number 89 which coprime

so x = 89  is the ans.

Q2014/098) Given a^2+b^2=16, c^2+d^2=25 find the maximium of ac

without loss of generality we can choose
a=4\sin\,t
b=4\cos\,t
c=5\sin\,p
d=5\cos\,p


so we get ad-bc= 20\sin\, t \cos\, p - 20\sin\, p \cos\, t = 20\sin (t-p) = 20
or \sin(t-p) = 1
so t= p+ \dfrac{\pi}{2}
hence
ac = 20 \sin \, t \sin \ p
= 20 \sin\, p + \sin (\dfrac{\pi}{2}+ p)
= -20 \cos \, p \sin\, p
= -10 \sin 2p


clearly the largest value is 10 and smallest -10

2014/097) If x^2-2x +4 has roots a and b then show that a^n + b^n = 2^{n+1} \cos\dfrac{\pi}{3} for n positive integer



We have as a and b are roots
a+ b= 2 and ab = 4
so a +b = 2 = 2^2 \cos \dfrac{\pi}{3} true for 1
(a^2+b^2) = (a+b)^2 – 2ba = 4 – 8 = -4 = 8 * \cos \dfrac{2\pi}{3} true for 2
Let it be true for n =k
We shall prove it by induction
(a^k+b^k)(a+b) = a^{k+1} +b^{k+1} + ab(a^{k-1} +b^{k-1})
Or 
a^{k+1}+b^{k+1}= (a^k+b^k)(a+b)-ab(a^{k-1}+b^{k-1})

we have

a^{k+1}+b^{k+1}= (a^k+b^k)(a+b)-ab(a^{k-1}+b^{k-1})
= 2^{n+1} \cos \dfrac{n\pi}{3} 2^2 \cos \dfrac{\pi}{3} – 4(2^n \cos\dfrac{(n-1)\pi}{3})
= 2^{n+2}( 2\cos \dfrac{n\pi}{3} \cos \dfrac{\pi}{3}) – 4(2^n \cos\dfrac{(n-1)\pi}{3})
= 2^{n+2}( \cos \dfrac{(n+1)\pi}{3} + \cos \dfrac{(n-1)\pi}{3}) – 2^{n+2} \cos\dfrac{(n-1)\pi}{3}
=
2^{n+2}\cos \dfrac{(n+1)\pi}{3} +2^{n+2} \cos \dfrac{(n-1)\pi}{3} – 2^{n+2} \cos\dfrac{(n-1)\pi}{3}
2^{n+2}\cos \dfrac{(n+1)\pi}{3}

We have proved the step for induction
Hence proved




2014/096) Evaluate 2\cos^3 \dfrac{\pi}{7}-\cos^2 \dfrac{\pi}{7}-\cos \dfrac{\pi}{7}

2\cos^3 \dfrac{\pi}{7}-\cos^2 \dfrac{\pi}{7}-\cos \dfrac{\pi}{7}
\cos \dfrac{\pi}{7}(2\cos^2 \dfrac{\pi}{7}-\cos \dfrac{\pi}{7}-1)
= -  \cos \dfrac{\pi}{7}(\cos \dfrac{\pi}{7} -  (2\cos^2 \dfrac{\pi}{7}-1))
= -  \cos \dfrac{\pi}{7}(\cos \dfrac{\pi}{7} -  \cos \dfrac{2\pi}{7})
=  - 2 \cos \dfrac{\pi}{7}\sin \dfrac{3\pi}{14}  \sin\dfrac{\pi}{14}

=  -\dfrac{ 2 \cos \dfrac{\pi}{7}\sin \dfrac{3\pi}{14}  \sin\dfrac{\pi}{14} \cos \dfrac{\pi}{14}}{ \cos \dfrac{\pi}{14}}
=  -\dfrac{  \cos \dfrac{\pi}{7}\sin \dfrac{3\pi}{14}  \sin\dfrac{\pi}{7}}{ \cos \dfrac{\pi}{14}}
=  -\dfrac{  2\cos \dfrac{\pi}{7}\sin \dfrac{\pi}{7}  \sin\dfrac{3\pi}{14}}{2 \cos \dfrac{\pi}{14}}
 = -\dfrac{  \sin  \dfrac{2\pi}{7} \sin\dfrac{3\pi}{14}}{2  \cos \dfrac{\pi}{14}}
 =- \dfrac{  \sin  \dfrac{2\pi}{7} \cos (\dfrac{\pi}{2} - \dfrac{3\pi}{14})}{2  \cos \dfrac{\pi}{14}}
= - \dfrac{  \sin  \dfrac{2\pi}{7} \cos \dfrac{2\pi}{7}}{2  \cos \dfrac{\pi}{14}}
= - \dfrac{ 2 \sin  \dfrac{2\pi}{7} \cos \dfrac{2\pi}{7}}{4  \cos \dfrac{\pi}{14}}
= -\dfrac{  \sin  \dfrac{4\pi}{7}}{4  \cos \dfrac{\pi}{14}}
= - \dfrac{  \cos(  \dfrac{\pi}{2}- \dfrac{4\pi}{7})}{4  \cos \dfrac{\pi}{14}}
= -\dfrac{  \cos  \dfrac{-\pi}{14}}{4  \cos \dfrac{\pi}{14}}
= - \dfrac{  \cos  \dfrac{\pi}{14}}{4  \cos \dfrac{\pi}{14}}
= - \dfrac{1}{4}